LRAPP Test Bed Array Cable Failure Analysis - Balaban, Martin M. (1971)
The report is a diagnosis of the LRAPP Test Bed array cable failure. The high risk aspects of the Test Bed implantment that are identifiable with the array cable's properties or its handling are considered, and the particular cable properties which had major influence on the implantment are identified and their effect analyzed. Methods for retrieval of the Test Bed are discussed and recommendations are provided for enhancing the certainty of success for future suspended array implantments.